2021
DOI: 10.1002/ijgo.14057
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based study of the relationship between advanced maternal age and premature/early‐term birth in Brazil

Abstract: Objective To verify whether advanced maternal age (AMA), defined as women of ≥35 years, is associated with premature and early‐term birth in Brazil, according to the onset of labor (spontaneous or provider‐initiated). Methods Cross‐sectional population‐based study. The “Birth in Brazil” study interviewed 23 894 puerperal women between 2011 and 2012, in all regions of Brazil. The current analysis included 17 994 adult mothers and their newborns (15 448 aged between 20–34 years, and 2536 ≥ 35 years). A propensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(61 reference statements)
2
1
0
Order By: Relevance
“…According to data from the National Institute of Statistics, the prematurity rate represents 6.5-9% of all births, and may increase to and reach 12.5% in reference centers. We compared the prematurity rate obtained in our study with that published by other work groups and found similar results, with a rate of pre-term birth around 10.24% [13,14].…”
Section: Prematuritysupporting
confidence: 82%
“…According to data from the National Institute of Statistics, the prematurity rate represents 6.5-9% of all births, and may increase to and reach 12.5% in reference centers. We compared the prematurity rate obtained in our study with that published by other work groups and found similar results, with a rate of pre-term birth around 10.24% [13,14].…”
Section: Prematuritysupporting
confidence: 82%
“…According to data from the National Institute of Statistics, the prematurity rate represents 6.5-9% of all births and may increase to and reach 12.5% in reference centers. We compared the prematurity rate obtained in our study with that published by other work groups and found similar results, with a rate of pre-term birth around 10.24% [36,37].…”
Section: Prematuritysupporting
confidence: 82%
“…A recent study shows the same conclusions; it assessed the association between maternal age and prematurity and found no increase in maternal age among pregnancies that terminated spontaneously, while they demonstrated a rise in prematurity with increased maternal age among pregnancies that required a planned delivery due to associated medical complications. Therefore, there was a correlation between increased maternal age and prematurity but as a result of maternal medical conditions that required planned delivery [ 36 ].…”
Section: Discussionmentioning
confidence: 99%